Fatores associados ao baixo peso ao nascer em um hospital referência na Amazônia. - OHANA, Giselle Jones (2022)
Introduction: Low birth weight is the main factor associated with risk of death in the neonatal period and it is important for public health because the frequency which it occurs, with the highest rates, up to 95.6%, are observed in countries under development. In Brazil, representing 8.2% of live births and Para is the 8th largest state with the number of newborns with low birth weight. Studies suggest as the main factors for low birth weight in our country the maternal pre-gestational disease, preeclampsia, genitourinary infections, low educational level of pregnant, unemployment, smoking and drug use during pregnancy, lack of prenatal care and preterm birth before. Thus, the search for these risk factors exist in an attempt to develop interventions that can reduce and prevent the occurrence of low birth weight. Objective: To identify factors that effectively interfere with low birth weight infants comparing underweight and not underweight in a reference hospital in the Amazon. Method: A case-control study with women who had their parturitions attended in a reference hospital in the Amazon. The information collection was performed at random from October to December 2010 through a questionnaire and were assessed demographic, socioeconomic and obstetric variables. In univariate analysis, was obtained for the whole group and separately in two samples of infants studied, the frequency distributions, measures of dispersion and central tendency of the variables studied. For a more detailed investigation of risk factors, we used the bivariate analysis by calculating odds ratio (OR) with confidence interval (CI) 95%, and verified the statistical significance by chi-square ( 2 ) and/or Fisher exact test with an alpha level of 0.05 (5%). Results: They were statistically associated with low birth weight, gestational age 22 to 36 weeks (OR=22.85, 95% CI 11.7 to 44.6), maternal age greater than or equal to 35 years (OR=2.68, 95% CI 1.07 to 6.74), per capita income between the middle and a minimum wage (OR=2.08, 95% CI 1.04 to 4.16), maternal education to elementary school full (OR and CI indeterminate), hospitalization during pregnancy (OR=3.21, 95% CI 2.05 to 5.04). Conclusion: The results allowed to know the local situation and highlight the need for specific regional policies in promoting and health education.